A Role of U12 Intron in Proper Pre-mRNA Splicing of Plant Cap Binding Protein 20 Genes - Pieczynski, Marcin; Kruszka, Katarzyna; Bielewicz, Dawid; Dolata, Jakub; Szczesniak, Michal; Karlowski, Wojciech; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia (Frontiers in Plant Science, 2018)
The nuclear cap-binding complex (CBC) is composed of two cap-binding proteins: CBP20 and CBP80. The CBP20 gene structure is highly conserved across land plant species. All studied CBP20 genes contain eight exons and seven introns, with the fourth intron belonging to the U12 class. This highly conserved U12 intron always divides the plant CBP20 gene into two parts: one part encodes the core domain containing the RNA binding domain (RBD), and the second part encodes the tail domain with a nuclear localization signal (NLS). In this study, we investigate the importance of the U12 intron in the Arabidopsis thaliana CBP20 gene by moving it to different intron locations of the gene. Relocation of the U12 intron resulted in a significant decrease in the U12 intron splicing efficiency and the accumulation of wrongly processed transcripts. These results suggest that moving the U12 intron to any other position of the A. thaliana CBP20 gene disturbs splicing, leading to substantial downregulation of the level of properly spliced mRNA and CBP20 protein. Moreover, the replacement of the U12 intron with a U2 intron leads to undesired alternative splicing events, indicating that the proper localization of the U12 intron in the CBP20 gene secures correct CBP20 pre-mRNA maturation and CBP20 protein levels in a plant. Surprisingly, our results also show that the efficiency of U12 splicing depends on intron length. In conclusion, our study emphasizes the importance of proper U12 intron localization in plant CBP20 genes for correct pre-mRNA processing.